Effects of HCl pretreatment, drying, and storage on the stable isotope ratios of soil and sediment samples. (9th June 2016) - Kim, Min‐Seob; Lee, Won‐Seok; Suresh Kumar, K.; Shin, Kyung‐Hoon; Robarge, Wayne; Kim, Minseok; Lee, Sang Ryong
Abstract : Rationale: Stable isotope (δ 13 C, δ 15 N, δ 34 S values) analysis has become increasingly important for tracing contaminant sources in environments. Pretreatment of environmental samples allows accurate analysis of stable isotope ratios. The pretreatment of a sample and its subsequent preservation could either contaminate or create experimental artifacts affecting the validity of the resulting C/N ratios and the elemental isotopic contents of a sample. Methods: The effects of acid pretreatment (0.1, 0.5, 1, 2, 5, 13 M HCl) and exposure period (2, 6, 12, 24, and 48 h) on the stable isotopic ratios of marine sediment (MS), river sediment (RS) and terrestrial soil (TS) samples were evaluated. The effects of storage temperatures (–80, –20 and 2°C), storage duration (1 week, 1 to 12 months) and washing steps (1, 2, 3, 5, 7 or 12 times) on the stable isotopic ratios were also considered. The %C, %N and %S, as well as the δ 13 C, δ 15 N, and δ 34 S values, of each sample were measured using continuous flow Elemental Analyzer/Isotope Ratio Mass Spectrometry (EA/IRMS). Results: The HCl treatment was applicable for δ 13 C analysis. However, the acid concentration and duration of exposure that brought about total removal of carbonate for the three sample types varied; e.g. the TS sample required stronger acid and a shorter exposure time. Storage time also had an effect: the δ 13 C values were lower and the δ 15 N and δ 34 S values higher after storage for 300 days. Conclusions: HCl pretreatment effectively eliminates carbonates and thereby helps δ 13 C analysis of the organic fraction. HCl pretreatment is not recommended for δ 15 N and δ 34 S analysis. Freeze‐drying of samples is recommended rather than oven drying. A temperature‐dependent change in the isotopic ratios of long‐term stored samples was observed during this study; therefore, relatively short‐term storage (–80°C) of freeze‐dried samples is preferable. Copyright © 2016 John Wiley & Sons, Ltd.